Discovery of CC bond-forming and bond-breaking radical enzymes: enabling transformations for metabolic engineering. (October 2020) - Fu, Beverly; Balskus, Emily P
Graphical abstract: Highlights: Radical enzymes catalyze difficult CC bond-forming and bond-breaking transformations. Radical enzymes catalyzing unprecedented reactions continue to be discovered. The products of radical enzymes are often of high value. Understanding mechanisms of radical enzymes will aid metabolic engineering efforts. Abstract : Radical enzymes catalyze some of the most chemically challenging CC bond-forming and bond-breaking reactions. Advances in DNA sequencing have accelerated the discovery of radical enzymes from microbes, including radical S -adenosylmethionine (rSAM) enzymes, glycyl radical enzymes (GREs), and diiron enzymes. These enzymes catalyze various reactions that yield products of industrial relevance (e.g. aromatics, hydrocarbons, and natural product derivatives), making their incorporation into engineered metabolic pathways enticing. Elucidating the mechanisms of radical enzymes that cleave and construct CC bonds will enable further enzyme discovery and engineering efforts.